Unsteady Mixed Convection Flow over a Cylinder of Elliptic Cross Section near Forward Stagnation Point (MATEMATIKA, 2012)
The unsteady mixed convection flow over a cylinder of elliptic cross section when the major axis is horizontal (blunt orientation) or vertical (slender orientation) near forward stagnation point is studied. The unsteadiness is due to an impulsive motion on the free stream. The governing boundary layer equations are first reduced into a non-dimensional form, and then transformed into a set of non-similar boundary layer equations, which are solved numerically using an efficient implicit finite-difference method known as Keller-Box method. The numerical results are obtained for various values of the Prandtl number, Pr, the mixed convection parameter, and parameter for blunt and slender orientation, !. The effects of these parameters on velocity profiles, temperature profiles as well as Nusselt number are presented through graphs and tables. The results show that as the mixed convection parameter, is increased, the velocity of the fluid is increased but the temperature of the fluid is decreased, for both blunt and slender orientations. Furthermore, the slender orientation gives earlier separation times for opposing flow while there is no separation of flow detected for the assisting flow. Keywords: unsteady flow; mixed convection; cylinder of elliptic cross section; forward stagnation point. 2010 Mathematics Subject Classification: 76B99; 76R99.